Contextual income and incidence of disability: results of EpiFloripa Elderly Cohort - Ana Lúcia Danielewicz; Eleonora d'Orsi; Antonio Fernando Boing (Universidade de São Paulo, 2019)
ABSTRACT OBJECTIVE: Evaluate the association between contextual income and the incidence of disability in basic and instrumental activities of daily living. METHODS: This is a cohort study, with sample of elderly individuals (n = 1,196) residing in Florianópolis, state of Santa Catarina, Brazil. The incidence of disabilities was evaluated using reports of difficulty or inability to perform six basic activities of daily living and nine instrumental activities of daily living after four years. Contextual income was obtained from the 2010 Census. We conducted multilevel logistic regression analyses with adjustment models for individual variables. RESULTS: The incidence of disability in basic activities of daily living was 15.8% (95%CI 13.8-17.9) and in instrumental activities of daily living incidence was 13.4% (95%CI 11.6-15.5). We observed significant association between contextual income and incidence of disability in basic activities of daily living. Having as reference the elderly living in the lower income tercile, those who lived in the intermediary terciles and in that of highest income had 37% (95%CI 0.41-0.96) and 21% (95%CI 0.52-1.19) lower chances of developing disability, respectively. For the incidence of disability in instrumental activities of daily living we observed no statistically significant associations. CONCLUSIONS: Contextual income influences the development of disability in basic activities of daily living in the elderly and should be the subject of actions to reduce socioeconomic inequalities and promote longevity with independence.